Federal Scientific Agroengineering Center VIM, Moscow, Russian Federation - A. V. Mironova (Сельскохозяйственные машины и технологии, 2022)
The degradation of unused agricultural lands is noted to cause significant damage to agricultural production such as plot overgrowing with weeds, blackened surface layer emergence, the existing microrelief disturbance, soil self- compaction and acidification, soil infiltration properties deterioration, and water erosion. (Research purpose) The research aims to determine the technological and physical and mechanical properties of the blackened soils in the Ryazan region, being out of active use for 2-6 years. (Materials and methods) The parameters of various unused soil plots were studied in the Ryazan region: in particular, the composition of the herbage, the thickness of the blackened soil layer, the degree of soil blackening, its density and moisture, and infiltration properties. (Results and discussion) It was found that a 6-year increase in the period of overgrowth in an unused site leads to an increase in the amount of weeds. The most common species of many-year-old weeds are dog grass (Elymus caninus L) with the occurrence of 13 percent, field grass (Cirsium arvense L.) with the occurrence of 11 percent, creeping wheatgrass (Elitrigia repens L.) with the occurrence of 10 percent, shoot-forming vole (Agrostis stolonifera L.) with the occurrence of 9 percent. It was determined that an increase in the period of plot overgrowing from 2 to 6 years results in the soil recompaction, an increase in its density from 1.32 to 1.56 grams per cubic centimeter, the blackened soil layer thickening from 3 to 11 centimeters, an increase in the soil blackening degree from 13 to 44 grams per cubic decimetre. It was found that the coefficient of variation in the soil blackening degree decreases from 21.0 to 5.1 percent, and the coefficient of variation in the blackened soil layer thickness declines from 25.3 to 6.6 percent. (Conclusions) The dependence between the soil infiltration intensity and its blackening degree was established: even being waterlogged in the blackened upper layer (0-10 centimeters), with the absolute moisture of 45 percent, this indicator remains within 20-25 percent in the lower layer (20-30 centimeters).